2010
DOI: 10.1016/j.msea.2010.06.085
|View full text |Cite
|
Sign up to set email alerts
|

Grain refinement of pure Ti during plastic deformation

Abstract: a b s t r a c tThe mechanism of grain refinement was studied in titanium subjected to high-rate surface mechanical attrition treatment. By cross-sectional transmission electron microscopy, the deformation structures were systematically characterized in a nanocrystalline (NC) layer of the treated surface which exhibits a grain size gradient. The microstructural evolution with increasing strain involves (1) the formation of slip bands with dislocation-free cells in their interiors, (2) nucleation and migration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The cell structure can be considered as a 'precursor' of the eventually developing grain structure, as have been experimentally observed in the UFG microstructures pro duced by the SPD processes [5,7,[31][32][33][34][35][37][38][39]50]. The cell structure can be considered as a 'precursor' of the eventually developing grain structure, as have been experimentally observed in the UFG microstructures pro duced by the SPD processes [5,7,[31][32][33][34][35][37][38][39]50].…”
Section: Determination Of Materials Parametersmentioning
confidence: 70%
See 1 more Smart Citation
“…The cell structure can be considered as a 'precursor' of the eventually developing grain structure, as have been experimentally observed in the UFG microstructures pro duced by the SPD processes [5,7,[31][32][33][34][35][37][38][39]50]. The cell structure can be considered as a 'precursor' of the eventually developing grain structure, as have been experimentally observed in the UFG microstructures pro duced by the SPD processes [5,7,[31][32][33][34][35][37][38][39]50].…”
Section: Determination Of Materials Parametersmentioning
confidence: 70%
“…Figure 1 shows the transmission electron micro scope (TEM) images of CP Ti workpieces produced by (a) and (b) orthogonal cutting [5], (c) and (d) multipass cold rolling [31], (e) ten-pass ECAP plus cold rolling with 77% thickness reduction [32], (/) two-pass ECAP [33], (g) multipass hydrostatic extrusion [34] and (h) surface mechanical attrition treatment (SMAT) proc esses [35], Figure 1(a) shows a TEM micrograph of a chip machined with the +20 deg rake angle tool, which microstructure consists of sub-lOOnm dislocation cells/grains interspersed with elongated, less developed subgrain structures. A dislocation cell structure with high dislocation den sity is often observed in CP Ti workpieces treated by a variety of SPD processes.…”
Section: Grain Refinement Of Cp Ti Through Spdmentioning
confidence: 99%
“…The mechanism of DRX may be classified into migrational and rotational types [39] where it was reported that primarily migrational DRX operates in metals subjected to static deformation or low strain rate dynamic deformation [27,40,41]. Nevertheless, in deformation at very high strain rates, there is insufficient time for long-range migration of the boundaries so that the DRX operates via the rotation of subgrain boundaries [40,42].…”
Section: The Recrystallization Mechanismmentioning
confidence: 99%
“…It has been demonstrated that dislocation motion and the value of the activation volume both vary with grain size during plastic deformation [46] and for CP Ti the magnitudes of V* were estimated as ~276b 3 , ~57b 3 and ~5b 3 for CG, UFG and NC Ti, respectively [47]. Although a reduction in grain size gives rise to an enhancement in stress, nevertheless this rise becomes less important when considering the drastic increase in the dislocation density in the coarser grains so that an increase in m with decrease in grain size is observed in the CP Ti.…”
Section: Strain Rate Sensitivitymentioning
confidence: 99%